Thermo-mechanical fe-demo based calculations of high entropy alloys (HEAs) (Fe-Ni-Cx (x=0.3-0.5) ternary alloy system using calphad method - Waseem Ullah shah; Dil Faraz khan; Haiqing yin (Kuwait Journal of Science)
The given research shows the thermodynamic analysis and calculation of the basic thermal properties of the high entropy alloy Fe-Ni-Cx (x=0.3-0.5) of concentration. The system is investigated through Thermo-calc package with FEDAT databases and Calphad method. The evaluation of interactions is found maximum at 0.04070 J/m2 of interfacial energy in the Fe-Ni-C ternary alloy system. The FCC_A1 phase is found the phase associated with highest molar volume in the Fe-Ni-Cx (x=0.3-0.5) ternary alloy system. The phase FCC_A1 is having austenite coordination with increasing density and apparent heat capacity. The temperature variation results the composite phases to be disappears with required level. The system is found highest apparent heat capacity 0.39269 J/mol. The density of phases becomes constant and it indicates the rare temperature withstanding phases. The fluctuations in the density of phases are changing with temperature as a result of phase’s nature and stability. The better magnetic properties are found for Basic centered cubic structure with highest interfacial energy. The alloy shows better magnetic coordination and thermodynamic properties enhancement for further analysis.